IMPLEMENTASI E-LEARNING MADRASAH: ANALISIS KESIAPAN SDM DAN INFRASTRUKTUR TEKNOLOGI INFORMASI - Ma'fiyah Ma'fiyah; Endah Mawarny; Yunus Yunus (STKIP Pesisir Selatan, 2026)
This research is motivated by the digital transformation in the madrasa environment that demands adaptive infrastructure and human resource (HR) capacity. The purpose of this study is to analyze the implementation of e-learning and the readiness of information technology infrastructure and HR at the State Madrasah Aliyah (MAN) in Palopo City. This study uses a descriptive qualitative approach. Data were collected through participant observation, in-depth interviews, and documentation studies involving the madrasah principal, teachers, and students as key informants. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions according to the interactive model of Miles and Huberman. The results of the study indicate that: (1) The implementation of the Educational Management Information System (SIMDIK) has been integrated through the SIMPATIKA application, madrasah e-learning, and the Madrasah Digital Report (RDM); (2) The effectiveness of learning through online assignments is highly dependent on teacher skills in operating application features and making innovative instructional modifications; (3) Infrastructure constraints in the form of limited internet access and server stability are the main technical obstacles that require adaptive solutions; (4) Parental support at home is a crucial factor in determining the success of internalizing values ​​and students' academic achievement in the digital ecosystem.